2019
DOI: 10.1002/nop2.378
|View full text |Cite
|
Sign up to set email alerts
|

Institutional delivery service use and associated factors among women who delivered during the last 2 years in Dallocha town, SNNPR, Ethiopia

Abstract: AimTo determine the institutional delivery service use and identify factors associated among women who delivered during the last two years in Dallocha town.DesignA community‐based cross‐sectional study.MethodsThe study was conducted from 10 March–10 April 2016. A total of 411 study participants were selected by using systematic sampling method. The source population was all reproductive age group mothers. Bivariate and multiple logistic regression was conducted.ResultsInstitutional delivery was 304 (74%). Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
4
10
0
Order By: Relevance
“…The proportion of institutional delivery was 76%, 95% CI (72.4%-79.7%). This finding was in line with 74%, 15 74.4%, 22 78.3%, 2 78.8% 16 studies conducted in Ethiopia and 78.1% in Gambia. 20 It was higher than 12.3%, 8 16.9% 29 24.8%, 5 26.2%, 19 31.0%, 9 32.8%, 30 47.3%, 18 63.1%, 31 64.62%, 14 64.8%, 21 71.2% 13 studies conducted in Ethiopia and 67.3% in Tanzania.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The proportion of institutional delivery was 76%, 95% CI (72.4%-79.7%). This finding was in line with 74%, 15 74.4%, 22 78.3%, 2 78.8% 16 studies conducted in Ethiopia and 78.1% in Gambia. 20 It was higher than 12.3%, 8 16.9% 29 24.8%, 5 26.2%, 19 31.0%, 9 32.8%, 30 47.3%, 18 63.1%, 31 64.62%, 14 64.8%, 21 71.2% 13 studies conducted in Ethiopia and 67.3% in Tanzania.…”
Section: Discussionsupporting
confidence: 90%
“…8,[10][11][12][13] The factors associated with institutional delivery are multiple and include age, income status, education, occupation, religion, residence, attending ANC, frequency of ANC visit, age at first marriage, age at first pregnancy, types of pregnancy (planned/unplanned), gravidity, parity, owing radio and/or television, knowledge, and occurrence of pregnancy danger signs. 1,2,5,8,9,[14][15][16][17][18][19][20][21][22][23] Ethiopia is one of the six countries that contribute to more than 50% of global maternal deaths. 24 Despite it is known that delivery attended by a skilled provider at a health facility reduced maternal deaths, but more than half of all births in Ethiopia take place at home.…”
Section: Introductionmentioning
confidence: 99%
“…The link between high ANC4 rates and high institutional delivery attendance has been documented [25][26][27][28]. Given this, our findings suggest that the significant decrease in institutional delivery is likely not due to women choosing not to deliver in health facilities, but rather, not being physically capable of reaching the health facility in time.…”
Section: Discussionsupporting
confidence: 53%
“…37 However, a study in Dallocha town, SNNPR, Ethiopia, confirmed the association between the number of ANC visits and home delivery in other settings. 37 , 38 Women with fewer ANC visit might be less likely to get more information about risks and problems that they might encounter during childbirth.…”
Section: Discussionmentioning
confidence: 99%